2018
DOI: 10.1136/bmjopen-2017-020945
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position, symptoms of depression and subsequent mental healthcare treatment: a Danish register-based 6-month follow-up study on a population survey

Abstract: ObjectiveExamine whether the severity of symptoms of depression was associated with the type of mental healthcare treatment (MHCT) received, independent of socioeconomic position (SEP).DesignRegister-based 6-month follow-up study on participants from the Danish General Suburban Population Study (GESUS) 2010–2013, who scored the Major Depression Inventory (MDI).ParticipantsNineteen thousand and eleven respondents from GESUS.InterventionsThe MHCT of the participants was tracked in national registers 4 months pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 50 publications
1
23
2
Order By: Relevance
“… 12–14 However, few studies have focused on initiation of mental healthcare among newly identified screen-positive individuals. 18–20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12–14 However, few studies have focused on initiation of mental healthcare among newly identified screen-positive individuals. 18–20 …”
Section: Discussionmentioning
confidence: 99%
“…Initiation of mental healthcare following population-based 18 or GP-based 19 20 screening ranges from 16% 19 to 42%. 20 The studies differ in three important ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, increased antidepressant use in the over-indebted might also reflect factors other than psychological morbidity. On the one hand, some studies suggest that prescribing bias might lead to a higher likelihood of pharmacological treatment for patients with lower socioeconomic status [30,34,35]. However, available evidence of an association between standard SES measures and antidepressant use is inconsistent [27][28][29][30].…”
Section: Plos Onementioning
confidence: 99%
“…Still, it is also possible that they may not have been able to reach out for support, which has previously been reported among 10% of patients with depressive symptoms who did not seek mental health services. 32 One previous study found that bereaved people were more likely to seek mental health care during bereavement if they had discussed psychological issues with a health professional before bereavement. 33 An invitation to a designated appointment from health professionals was regarded as positive and helpful among family caregivers in a qualitative study, regardless of the family caregivers' need for support.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%